- #1

sparkle123

- 175

- 0

d[A]/dt=-(k+k`)[A]+k`[A]0

The solution of this first-order differential equation is:

[A]= (k`+ke^(k`+k)t)*[A]0/(k`+k)

Could you please explain how you get from the first equation to the second? THANKS!

btw: if this helps, this is part of the solution for a chemical kinetics (rates/equilibrium) problem

so A is the reactant, t is the time, and k and k` are the rate constants for the reaction A==B

The solution of this first-order differential equation is:

[A]= (k`+ke^(k`+k)t)*[A]0/(k`+k)

Could you please explain how you get from the first equation to the second? THANKS!

btw: if this helps, this is part of the solution for a chemical kinetics (rates/equilibrium) problem

so A is the reactant, t is the time, and k and k` are the rate constants for the reaction A==B

Last edited: